2020
DOI: 10.1186/s12888-020-02657-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of patient-provider communication: a qualitative study of patient attitudes regarding co-occurring depression and chronic diseases in Malawi

Abstract: Background: Globally, depression is a leading cause of morbidity and mortality particularly in Low and Middle-Income Countries (LMICs). The burden of non-communicable diseases (NCDs) are also increasing in LMICs, the conditions frequently co-occur and exacerbate NCD outcomes. Depression interventions alone are not effective at improving NCD outcomes, resulting in wide-reaching calls for integrated services. Integrated services are in a nascent phase in LMICs in general and in Malawi in particular. This manuscr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Further, participants indicated that their understanding of depression as an illness began with treatment initiation, and their understanding of depression as a medical condition was associated with reduced stigma in qualitative and quantitative assessments within the domains of treatment carryover and negative affect. These observations are consistent with prior research suggesting that patients who understand depression to be a medical condition are more likely to be amenable to medical treatment [ 25 , 51 , 52 ]. Understanding depression as an illness was not associated with disclosure scores, which were more often driven by patients’ direct experiences with disclosure and social support.…”
Section: Discussionsupporting
confidence: 90%
“…Further, participants indicated that their understanding of depression as an illness began with treatment initiation, and their understanding of depression as a medical condition was associated with reduced stigma in qualitative and quantitative assessments within the domains of treatment carryover and negative affect. These observations are consistent with prior research suggesting that patients who understand depression to be a medical condition are more likely to be amenable to medical treatment [ 25 , 51 , 52 ]. Understanding depression as an illness was not associated with disclosure scores, which were more often driven by patients’ direct experiences with disclosure and social support.…”
Section: Discussionsupporting
confidence: 90%
“…Two patients from each of the same 10 hospitals in this study were interviewed one-on-one. Patients did not tend to describe mild or moderate depression as a medical condition, and instead thought of it more as a normal part of life [ 37 ]. Because of this, the patients described the power of their providers to shape how a patient might react to depression screening, diagnosis, and treatment [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients did not tend to describe mild or moderate depression as a medical condition, and instead thought of it more as a normal part of life [ 37 ]. Because of this, the patients described the power of their providers to shape how a patient might react to depression screening, diagnosis, and treatment [ 37 ]. Patients in another study done in Malawi described depression as looking sad or different than usual, self-isolation, ‘thinking too much’, and anger [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of empathy may explain the distrust in expertise and motives of providers [ 25 ]. Consequently, the patients–provider relationship is suboptimal and diminishes the quality of knowledge transfer and care [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%